(untitled) (Praxis Educativa, 2018)
The aim of this paper is to address some educational issues regarding some school´s transformations that have irrupted into the scholar field on this specially chosen conjuncture from our Recently History. In order to do this, we will be interested in asking which kind of educational problematics have effectively taken place at school and have also operated as a sort of “before and after” starting point for re thinking daily life at school and the teaching training as well.